Decision Support System for Selection of Superior Crystal Guava Seeds with SMART Method - Yuliyana; Muslimin B; Suci Ramadhani (Politeknik Pertanian Negeri Samarinda, 2022)
Crystal guava is one of the horticultural plants that play a role in meeting food needs, the horticultural sector is also able to contribute to domestic income. The purpose of this study was to produce a Decision Support System for the Selection of Crystal Guava. By using the PHP programming language and the database using MySQL and using the waterfall model for system development and Unified Modeling Language (UML) for system design. In this study, the data collection techniques used were literature study, observation and interviews. The result of this research is a decision support system is made to determine the proper selection of Crystal Guava Seeds. Users can input alternative data, view criteria data. Then the system will find a solution using the SMART method. After the decision is obtained, the system will display the final result of the calculation.